SAJUMPUT MENDUNG PUTIH (Transformasi Terlihat Menjadi Terdengar) - Fatimah, Mutiara Dewi (Institut Seni Indoensia Surakarta, 2018)
In Javanese tradition, batik is an art. In terms of its creation to application, batik is very close to life, likewise with one of these phenomenal batik, which is jumputan. A rare event is now transforming like mushrooms in the rainy season. The cloth which was used to be worn by lower class society is now an idol among the upper class society. By carrying the Javanese concept in a song namely the song of Winengku Sastra, the composition of this music was created.This research attempted to use phenomenological and ethnographic studies in reviewing, dissecting and analyzing the event. Phenomenology is expected to be able to unravel the logical reasons for past and present views including placing them in the frame of the phenomenon of musical performances. Meanwhile, ethnography is expected to be able to review and describe in detail the fabric structure into distinctive music. Likewise the musical concept will be carried in this work, namely the concept of transmedia instrument. Keywords: Jumputan, Society, and Music.